Knowledge and Adherence to Weekly Iron and Folic Acid Supplementation Among Adolescent Girls of Selected Government Schools - Regmi, Babita; Onta, Mandira; Subedi, ishwar (Journal of Food Science and Technology Nepal, 2024)
Anaemia is a global public health problem and is the common cause of morbidity and mortality in adolescent girls. World Health Organization recommends weekly iron-folic acid supplementation to reduce anaemia in adolescent girls. The significance of this work is to find out knowledge and adherence to weekly iron and folic acid supplementation among adolescent girls of selected government schools. A descriptive cross-sectional research design was used to conduct the study among 324 adolescent girls studying in grades eight to ten of selected government schools in Kathmandu. Probability, cluster sampling technique was used, and data was collected by using a structured self-administered questionnaire and analyzed by using descriptive statistics as frequency, percentage, mean, and standard deviation and inferential statistics as chi-square test. The study reveals that less than half of the respondents (47.8%) had adequate adherence to weekly iron and folic acid supplementation among adolescent girls. Similarly, less than half of the respondents (44.1%) had an adequate level of knowledge on anaemia. There was a statistically significant association between adherence status to weekly iron and folic acid supplementation and both mothers (p=0.004) and fathers’ (p=0.002) educational status and mothers’ occupation (p=0.024) respectively which shows that the adherence status to weekly iron and folic acid supplementation and level of knowledge on anaemia is inadequate. Thus, a more awareness programme on anaemia and the importance of iron and folic acid supplementation, better parental involvement in education sessions and close monitoring by concerned authorities is needed.